Finance and economy for society : integrating sustainability - Alijani, Sharam; Karyotis, Catherine (United Kingdom : Emerald, 2017)
The latest volume of Critical Studies on Corporate Responsibility, Governance and Sustainability examines the social, economic and environmental impacts of corporations, and the real effects of corporate governance, CSR and business sustainability on societies in different regions.--
Includes bibliographical references and index.
BBS
Karim International
Keywords: Finance -- History; Capitalism -- History; Capitalism; Finance; Business & finance